Isolation and Detection of Biofilm Producing Pseudomonas aeruginosa from Suspected Urinary Tract Infections in Dogs and Its Resistance to Antibiotics - Jasim, Shatha; M Hayyawi, Sahar (The Iraqi Journal of Veterinary Medicine, 2025)
This study aimed to determine the relationship between the biofilm formation in Pseudomonas aeruginosa and the protein concentration ins it, as well as to determine the resistance of this bacterium to antibiotics. A total of 108 urine samples were collected from suspected urinary tract infections (UTIs) in dogs, conducting general urine examination (GUE) to detect the infection, isolation, and identification the bacteria based on traditional diagnostic tests, the VITEK-2 system, and polymerase chain reaction (PCR) targeting the 16S rRNA gene. The study involved determining the antibiotic susceptibility of the isolates against ten antibiotics, determination of the biofilm layer by the tube method and Congo red method, evaluation of the strength of biofilm by microtiter plate, and detection of the biofilm protein concentration by Bradford method. The total number of P. aeruginosa isolates was 6/108 (5.5%), among which the isolates that produced the biofilm were 5/6 (83.33%). These isolates were confirmed by the VITEK-2 assay followed by the PCR and sequencing of the amplicon that validated the identity of the isolates, with 99% similarity to P. aeruginosa reference sequences, and the sequences were deposited in NCBI GenBank (accession numbers PP979721.1–PP979726.1). Analysis showed a strong positive correlation (r = 0.998) between the biofilm formation and the protein concentration. All isolates demonstrated 100% resistance to amikacin, trimethoprim, cefotaxime, amoxicillin/clavulanic acid, ampicillin, cephalexin, and lincomycin, and 33% were resistant to gentamicin, while 100% were sensitive to ciprofloxacin. In conclusion, these findings underscore a significant correlation between biofilm formation and protein concentration. The knowledge of bacterial ability to form biofilms and their antibiotic resistance pattern is important to improve veterinary practices and prescription of the appropriate antibiotic in the context of UTIs in dogs‎‎‎.